One, Two Buckle My Shoe - Punter, Russell; Illustraed by David Semple (London Usborne, 2010)
This is a new title in the fantastic "First Reading Series", part of the Usborne Reading Programme. It is aimed at children who are beginning to read. It includes the classic English counting rhyme, which children will want to hear again and again. It is developed in consultation with Alison Kelly, who is Principal Lecturer in Education from Roehampton University and an early reading specialist. Every title in this series features clear and compelling text accompanied by charming and highly appealing illustrations. It is designed to motivate children as they learn to read.
Include Color Illustrations
Keywords: Nursery rhymes, English